Evaluating a novel dietary diversity questionnaire to assess dietary diversity and adequacy of New Zealand women. - Kruger R; Hepburn AJ; Beck KL; McNaughton S; Stonehouse W (Elsevier Inc, 2021)
Objectives We sought to develop and evaluate the relative validity of a dietary diversity questionnaire (DDQ) that reflects food-group diversity, food variety, and micronutrient adequacy among New Zealand women. Methods A cross-sectional study included New Zealand women (Auckland based; ages 16–45 y, n = 101), completing a 7-d DDQ and 4-d weighed food record (reference method). The relative validity of the DDQ was evaluated by correlating nutritious and discretionary dietary diversity scores (DDSs; number of food groups) and food-variety scores (number of foods), calculated from both methods. The dietary mean adequacy ratio (MAR; micronutrient intakes relative to estimated average requirements) was calculated from the weighed food record and correlated to dietary diversity and food-variety scores from the DDQ to assess construct validity. Cross-tabulation was used to explore dietary diversity measures versus adequacy ratios. Significance was set at P < 0.05. Results The median (interquartile range) DDSs (maximum 25) from the DDQ—23 (21–23)—and the weighed food record—18 (17–19)—were significantly correlated (rs = 0.33, P < 0.001), as were the food-variety scores (maximum 237)—respectively, 75 (61–87) and 45 (37–52) (rs = 0.22, P < 0.03). A mean (± SD) MAR of 0.94 ± 0.04 suggested a near-adequate diet, but one-third of foods consumed were from discretionary sources. Nutritious DDS was significantly correlated with MAR for micronutrients (rs = 0.20, P ≤ 0.05). An inverse trend was observed between discretionary DDS and MAR. Conclusions The DDQ is a quick, low-burden tool for describing nutritious and discretionary dietary diversity reflecting micronutrient adequacy in high-income settings. It requires further validation across different time frames, population groups, and settings.
Keywords: Diet quality; Discretionary food; Food variety; Food-group diversity; High-income setting; Micronutrient adequacy; Nutritious food; Adolescent; Adult; Cross-Sectional Studies; Diet; Eating; Female; Humans; Micronutrients; Middle Aged; New Zealand; Surveys and Questionnaires; Young Adult